Membangun Kemampuan Public Speaking dalam Meningkatkan Kepercayaan Diri Siswa Sekolah Dasar - Cahyadi, Marliza; Suriani, Ari; Nisa, Sahrun (Asian Journal of Early Childhood and Elementary Education, 2024)
Developing self-confidence is an essential aspect that needs to be nurtured in elementary school students from an early age. This research aims to explore ways to build public speaking skills to enhance self-confidence in elementary school students. This research employs a literature study approach by analyzing various relevant literature. The results show that public speaking skills can help students become more confident, express their opinions bravely, and communicate effectively. Teachers can implement innovative teaching methods such as role-playing, group presentations, and storytelling to practice these skills. Support from the students' surrounding environment also plays a crucial role in developing their self-confidence. This research concludes that building public speaking skills from an early age is essential for elementary school students to boost their self-confidence and prepare them to face future challenges.